Teacher, to learn, I need to move. (Journal of Parents and Teachers, 2025)
The article highlights the importance of transmitting and contributing to teacher training through the media. Therefore, within journalistic genres, there are several items or subdivisions: informative, opinion, and advertising. Additionally, the text should be understandable, engaging, clear, and concise. And, of course, it should include titles, subtitles, and headings.
Keywords: learn; innate; critical; thinking; educational system